2021
DOI: 10.3389/fmed.2021.754434
|View full text |Cite
|
Sign up to set email alerts
|

Novel Targets for Drug Use in Eosinophilic Granulomatosis With Polyangiitis

Abstract: Eosinophilic Granulomatosis with Polyangiitis (EGPA) is a rare autoimmune disease characterized by medium and small vessels inflammation. Cardiac vasculitic involvement is one of the most severe manifestations with a significant impact on patients' long-term prognosis: anyway, a specific therapeutic approach for heart involvement in EGPA has not been explored yet. Current regimen consists of a long-term therapy with high dose of glucocorticoids, causing the well-known related-adverse events; immunosuppressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The use of the anti-CD20 monoclonal antibody rituximab is conditionally recommended in current guidelines to induce remission in patients with active, severe EGPA (7,40). Ongoing trials will test the potential clinical benefits of using rituximab, reslizumab and benralizumab for the treatment of EGPA (56).…”
Section: Biologics For Systemic Eosinophilic Diseases: Egpa and Hesmentioning
confidence: 99%
“…The use of the anti-CD20 monoclonal antibody rituximab is conditionally recommended in current guidelines to induce remission in patients with active, severe EGPA (7,40). Ongoing trials will test the potential clinical benefits of using rituximab, reslizumab and benralizumab for the treatment of EGPA (56).…”
Section: Biologics For Systemic Eosinophilic Diseases: Egpa and Hesmentioning
confidence: 99%
“…A recent retrospective study showed Rituximab could be effective in treating relapses of EGPA vasculitis, with a higher remission rate in ANCA positive patients [34]. Other studies have shown Rituximab to be an effective glucocorticoid sparing agent [33], suggesting an alternative role in EGPA treatment (NCT02807103).…”
Section: Eosinophilic Granulomatosis With Polyangiitismentioning
confidence: 99%
“…Rituximab, an anti-CD20 monoclonal antibody, is approved for the induction and maintenance of granulomatosis with polyangiitis and microscopic polyangiitis. The mechanism of action is in part attributed to depletion of progenitors of ANCA producing plasma cells, in addition to targeting B-cell immune response [33]. A recent retrospective study showed Rituximab could be effective in treating relapses of EGPA vasculitis, with a higher remission rate in ANCA positive patients [34].…”
Section: Eosinophilic Granulomatosis With Polyangiitismentioning
confidence: 99%
“…Patients with EGPA can be genetically distinguished into 2 groups; the first group characterized by HLA-DQA1 polymorphisms has positive MPO-ANCAs, whereas the second group has no association with HLA-DQA1 and is MPO-ANCA negative [ 16 , 17 ]. Although EGPA is classified as an ANCA-associated vasculitis, the percentage of patients with ANCA (mostly MPO/p-ANCA) varies among several studies and fluctuates between 30 and 60% [ 7 , 16 , 18 ]. Nevertheless, all patients, regardless of their ANCA status, have eosinophilia and allergic background.…”
Section: Introductionmentioning
confidence: 99%